The Relevance of Psychophysical Methods Research for the Practitioner. (September 2017) - Fox, Robert R.; Maikala, Rammohan V.; Bao, Stephen; Dempsey, Patrick G.; Brogmus, George; Cort, Joel; Maikala, Rammohan V.
The use of a psychophysical methodology in conducting manual materials handling and upper extremity studies is well recognized, and the findings (e.g., the Snook and Ciriello studies and the Liberty Mutual tables) have extensive application in the assessment and design of a variety of tasks in industry. In particular, the psychophysical methodology is directed to the assessment of what workers can actually perform and as such has identified acceptable workloads for various working populations. In many cases the identification of these acceptable workloads has historically been very difficult to achieve with methods in other scientific disciplines (e.g., Biomechanics, Physiology, Epidemiology). The purpose of this discussion panel will be to explore the questions on the usefulness and continuing relevance of the psychophysical methodologies to address the needs of the practitioner community. Each panelist will explore the applications of psychophysics in several areas of research and practice. The continuing relevance and directions of psychophysical research will be explored in discussion with the panelists and audience.